Peran Pendidikan Jasmani, Olahraga, dan Kesehatan dalam Pembentukan Karakter dan Perkembangan Gerak Anak Sekolah Dasar - Rahmawati, Kesya Aprilia; Nurlia, Ririn; Oktavia, Rizqi; Ihsani, Virna Noor Adlida; Hafiza, Nadyne Dinda (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Physical Education, Sports, and Health (PJOK) plays an important role in supporting student growth and development through increased physical activity and the development of basic movement skills. Physical activity in PJOK learning brings significant changes in both physical, cognitive, mental, and emotional development. PJOK aims to be able to develop aspects of health, physical fitness, social skills, emotional stability, and critical thinking skills. This research uses a qualitative approach through the literature study method. Qualitative research is research that uses the natural environment as an explanation and emphasizes the search for meaning. This research is a data collection based on the results of journal literature studies published through google scholar. The data analysis process is carried out qualitatively with the stages of data reduction, data presentation, and conclusion drawn. The results of the analysis show that PJOK is part of an effort to instill character in children, such as discipline, responsibility, and sportsmanship. PJOK structured learning activities can contribute to balanced child growth and development, these movement activities can also increase muscle strength, endurance, agility, and balance. PJOK plays an important role in supporting student growth and development by increasing physical activity and developing basic motor skills